1969
DOI: 10.1172/jci106042
|View full text |Cite
|
Sign up to set email alerts
|

Parotid fluid cortisol and cortisone

Abstract: A B S T R A C T Parotid fluid corticosteroids, substantially comprised of cortisol and cortisone, were previously demonstrated to rise to far greater levels 4 hr after administration of ACTH than they did in the third trimester of pregnancy, although the plasma total corticosteroid concentrations were similar in these two states. It was therefore suggested that only nonproteinbound corticosteroid gains access to parotid fluid. In the present study parotid fluid cortisol and cortisone and plasma dialyzable cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…During surgical preparations, denial of the impending procedure may have been impossible, causing coping mechanisms to fail and plasma cortisol levels to increase greatly. In the present study measurements of salivary cortisol reflected the plasma levels, as has been shown in previous studies (21,22), suggesting that salivary measures can be satisfactorily substituted for plasma assays of cortisol.…”
Section: Discussionsupporting
confidence: 86%
“…During surgical preparations, denial of the impending procedure may have been impossible, causing coping mechanisms to fail and plasma cortisol levels to increase greatly. In the present study measurements of salivary cortisol reflected the plasma levels, as has been shown in previous studies (21,22), suggesting that salivary measures can be satisfactorily substituted for plasma assays of cortisol.…”
Section: Discussionsupporting
confidence: 86%
“…92 In studies using mass spec trometry, a very close corre lation has been shown between salivary cortisol levels and free serum cortisol concentrations before and after adrenal stimulation, and also following intra venous hydrocortisone administration in groups of patients with a wide range of serum cortisol-binding capacities (for example, patients with high CBG levels due to oestro gen treatment, patients homozygous for a nonfunctional CBG variant and healthy volunteers); the increase in salivary cortisol levels following adrenal stimulation was higher than that observed in total serum cortisol concentration. 49,[93][94][95][96] The idea that cortisol concentrations in saliva merely result from passive diffusion was subsequently challenged, mainly because of two distinct phenomena: firstly, the expression of 11β-HSD2 by the parotid glands 16 and, secondly, evidence that CBG is present in saliva at low concentrations, 97,98 although changes in CBG con centration do not have a detectable effect on salivary cortisol levels. 41,99,100 11β-HSD2 is probably a key determinant of salivary cortisol concentrations.…”
Section: Salivary Cortisol and Cortisonementioning
confidence: 99%
“…The single physiological consideration that has been found capable of distorting salivary steroid levels relative to free plasma levels is the metabolism of steroids within the salivary gland. Katz and Shannon, whose work in the 60s pioneered the study of salivary steroids, identified the presence of 11-beta-hydroxysteroid dehydrogenase in the parotids (Katz and Shannon, 1969;Ferguson and MacPhee, 1975), a n enzyme responsible for converting cortisol to cortisone, which is normally a negligible steroid in humans. This problem has not appeared to affect the utility of salivary cortisol assays, however (cf.…”
Section: Physiological Basis For Salivary Steroid Monitoringmentioning
confidence: 99%